Sex differences in brain activation to anticipated and experienced pain in the medial prefrontal cortex - Straube, Thomas; Schmidt, Stephanie; Weiss, Thomas; Mentzel, Hans-Joachim; Miltner, Wolfgang H. R. (Human Brain Mapping, 2009)
Previous studies on sex differences in neural responses to noxious stimuli yielded mixed results. Both increased and decreased brain activation in several brain areas in women as compared to men has been reported. The current event-related functional magnetic resonance imaging study used a parametric design with different levels of the intensity of electrical stimulation in order to investigate sex differences in brain activation during pain processing. Four intensity levels, which were determined individually according to subjective ratings, ranging from stimulation below the stimulus detection threshold to moderately painful stimuli, were applied. Females experienced mild and moderate pain at lower stimulus intensity than males. Pronounced sex differences in brain activation were found in response to stimulation below the detection threshold and for the most intense pain stimuli in the medial prefrontal cortex (MPFC). Under both the conditions, women showed stronger activation in a region of the pregenual MPFC, which has been implicated in introspective, self-focused information processing. The results suggest that women, as compared to men, show increased self-related attention during anticipation of pain and in response to intense pain. © 2008 Wiley-Liss, Inc. Key words: gender; brain; anticipation; insula; pain.
Created from Fastlane, Scopus look-up